Infection after ureteroscopy for ureteric stones: analysis of 71 305 cases in the Hospital Episode Statistics database. (12th August 2022) - Veeratterapillay, Rajan; Gravestock, Paul; Harding, Chris; Shaw, Matthew; Fitzpatrick, John; Keltie, Kim; Cognigni, Paola; Sims, Andrew; Rogers, Alistair
Abstract : Objectives: To investigate the burden of infectious complications following ureteroscopy (URS) for ureteric stones on a national level in England using data from the Hospital Episodes Statistics (HES) data warehouse. Materials and Methods: A retrospective cohort was identified and followed up in HES during the period April 2013 to March 2020 for all procedure codes relating to ureteroscopic stone treatment (M27.1, M27.2, M27.3). Treatment episodes relating to the first URS ('index ureteroscopy') for each patient were further analysed. All subsequent admissions within 30 days were also captured. The primary outcome was diagnosis of urinary tract infection (UTI; including all codes relating to a UTI/sepsis within the first 30 days of index URS). Secondary outcomes were critical care attendance, attendance at the accident and emergency department (A&E) within 30 days, and mortality. Results: A total of 71 305 index ureteroscopies were eligible for analysis. The median age was 55 years, and 81% of procedures were elective and 45% were undertaken as day‐cases. At the time of index URS, 16% of patients had diabetes, 0.5% had coexisting neurological disease and 40% had an existing stent/nephrostomy. Overall, 6.8% of the cohort ( n = 4822) had a diagnosis of UTI within 30 days of index URS (3.9% immediately after surgery). A total of 339 patients (0.5%) required an unplanned stay in critical care during their index URS admission; 8833 patients (12%) attended A&E within 30 days. Overall mortality was 0.18% (60 in‐hospital, 65 within 30 days); 40 deaths (0.056%) included infection as a contributing cause of death. Conclusion: We present the largest series evaluating infectious complications after ureteroscopic stone treatment. The procedure is safe, with low inpatient infective complication and critical care admission rates.